ANALISIS PENDAPATAN DAN KELAYAKAN USAHATANI TOMAT DI KELURAHAN BOYAOGE KECAMATAN TATANGA KOTA PALU - Saddam Fadli (Agroland: Jurnal Ilmu-ilmu Pertanian, 2014)
Large amount of tomato production in Boyaoge Village can not ensure the village farmers to have high income due to high fluctuations of fresh tomato price. This study aims were to identify tomato farmers’ income and  to determine the feasibility of tomato farm in Boyaoge Village, Tatanga District of Palu City The research was carried out during December 2013 to February 2014. Respondents were selected using a census method taking all the farmers populatin of 35 peoples. The results showed that the revenue generated by the tomato farmers in the Boyaoge Village Tatanga District Palu City was IDR 17,483,255.05 ha-1 planting season-1 (PS). The tomato farming system was found feasible to be developed in Boyaoge Village Tatanga District Palu City as indicated by the revenue cost ratio value (R/C-ratio) of 1.76. Key Words : Feasibility, income, and tomato.